Lecturer Internship Program in Industry to Provide Real Work Experience for University Students - Layta Dinira dan Deasy Chrisnia Natalia (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Indonesia higher education learning system is currently less responsive to the industrial jobdynamics. As a result, there is a mismatch between graduates’ skill with the competenciesrequired by industry. Higher education has prepared nearly one million students to becometeachers, but the government has no plans to increase the number of public servant teachers.This policy makes most of graduates are unemployed. Companies in non-education andmanufacturing services have started complaining about the difficulty of finding workerslike engineers to fill in skilled positions. The rapid changing of industrial job dynamicsmake learning in higher education institution should move as rapidly as possible with theindustry. Therefore, it is necessary to develop collaboration between higher educationinstitution and industry. This paper proposed an innovation to learn and develop knowledgefrom industry through lecturer internship program. After attending internship program inthe industry, lecturers are expected to provide more real working experience to the students.The lecturer internship program in the industry will be focused on product research anddevelopment collaboration. In this paper will be presented a theoretical study about: (1)thebenefits; (2)factors that can affect; or (3)hinder the success of lecturer internship program inthe industry.Keywords: [lecturer, internship, program, industry, university